Investigation Of Whole Duration And Submicrosecond Structure Of Uncommon Negative Cloud-To-Ground Flash - Mohamed Ismail, Abdul Rahim (2020)
This thesis potrayed analysis of uncommon negative cloud-to-ground flash by consider the whole duration of flashes which commonly were reported by majority of investigators to have less than 1 second. In order to get more understanding on these matters, the author attempted to identify and investigate the relationship of the fine structure of commencement (or also known as subsidiary peak) of the first return stroke with this uncommon profile . The subsidiary peak was suggested by the early investigator as current oscillation or by a reflection of a traveling wave in the return stroke just after its commencement. However, this subsidiary peak was not well understood in the scientific lightning study. This analysis is important as a scientific value for electromagnetic compatibility's community and lightning protection in designing a proper lightning detection system and lightning scheme protection. This thesis is also important in lightning comprehend the initiation process of lightning ground flashes. Therefore two locations have been selected for the measurement, Both two locations are in Paya Rumput Perdana, Melaka and Faculty of Technology Engineering (Universiti Teknikal Malaysia Melaka). The electric fields generated by lightning negative ground flashes were measured. The data were measured with nanosecond resolution using the combination of flat plate antenna, fast electric field buffer and high-speed recorder (Yokogawa DL850E and HDO 4040 LeCroy). The total of 938 flashes which composed of 799 negative ground flashes, 26 positive ground flashes and 113 cloud flashes were analyzed in term of on electric field (also known as fast electric field). From 51 out of 799 samples of negative ground flashes were considered rare where the duration of the flashes was uncommon case (6 %) which had the duration of more than 1 second. Furthermore. the number of strokes varies from 4 to 19 strokes. Next, the subsidiary peaks of 50 of uncommon samples were analyzed by using the terminology that has been introduced by Krider (1980). It was consistently shown the existence of small second peak or alpha (a) for all sample followed by several larger subsidiary peaks (a peak. b peak and c peak). Interestingly, this thesis reported the finding of new features of subsidiary peaks which have more than 5 larger of subsidiary peak. Statistically, all the features of alpha and other larger peaks were discussed in this thesis. From the first contribution of the thesis was found that the numbers of subsidiary peaks are depending on the duration of zero crossing. In addition, the secondary new contribution was found that the subsidiary peak is related with the number of the production of the return stroke, However, the higher numbers of subsidiary peak have no correlation with uncommon duration (more than 1 second).